Research on cow traction in Africa: Some lessons to be learnt - Jabbar, M.A. (International Livestock Centre for Africa, 1993)
This paper compares the conclusions drawn from ILCA's work on single-ox and cow traction in Africa with those drawn from surveys and farmers' experience in South East Asia especially Thailand and Bangladesh. The ILCA work shows cow traction to be apparently more profitable than single-ox ploughing and both better than pair-ox ploughing. This paper throws some doubt on these conclusions and indicates that cow traction may cause problems by requiring larger amounts of high quality feed. Also Asian experiences show that using poorly fed cows for draught work results in long term declines in fertility and milk production. Thus if only poor to medium quality feed is available the single-ox option may be the better one in Africa despite the fact that more cattle have to be kept overall.